2021
DOI: 10.3389/fmed.2021.776956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Repetitive Cardiac Output Measurements at Rest and End-Exercise by Direct Fick Using Pulse Oximetry vs. Blood Gases in Patients With Pulmonary Hypertension

Abstract: Background: Exact and simultaneous measurements of mean pulmonary artery pressure (mPAP) and cardiac output (CO) are crucial to calculate pulmonary vascular resistance (PVR), which is essential to define pulmonary hypertension (PH). Simultaneous measurements of mPAP and CO are not feasible using the direct Fick (DF) method, due to the necessity to sample blood from the catheter-tip. We evaluated a modified DF method, which allows simultaneous measurement of mPAP and CO without needing repetitive blood samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Table 1 summarises the studies comparing CO TD and CO DF in PcPH [ 2 , 3 , 4 ]. In total, 113 patients had pulmonary arterial hypertension (PAH) (group 1) patients and 21 patients had chronic thromboembolic PH (CTEPH).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 summarises the studies comparing CO TD and CO DF in PcPH [ 2 , 3 , 4 ]. In total, 113 patients had pulmonary arterial hypertension (PAH) (group 1) patients and 21 patients had chronic thromboembolic PH (CTEPH).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1 , the exact bias and 1.96 SD of bias between TD and DF in the context of PcPH is unknown and there is variability in the published studies. Possible explanations for the observed variability include: different severity and characteristics of PcPH patients, with lower mean CO in the study from Hoeper et al [ 2 ], and differences in the protocol of CO measurement using either TD or DF (e.g., average of two to three measurements for TD for Duknic et al [ 3 ], five measurements with deletion of highest and lowest values for TD for Hoeper et al [ 2 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TD is a reference method based on an analysis of 35 PcPH patients in 1999, which showed good agreement between TD and DF with a 2SD of bias of 1.1 L/min [ 3 ]. However, recent published data have shown that the agreement between DF and TD is probably lower than previously thought, with a wide range of PE (42% and 44.6%) and LoA (2SD of bias of 2.48 L/min), leading to misclassification in the prognosis assessment of patients with PAH and misclassification of exercise PH [ 28 , 29 , 30 ]. In this context, it is likely that TD might be the cause of the lack of agreement when we compared TD with MRI.…”
Section: Discussionmentioning
confidence: 99%